EFFECTS OF SMOKING ON LENGTH OF HOSPITAL STAY IN PATIENTS SURVIVING AN ORTHOTOPIC LIVER TRANSPLANT - Riyaz, Shahzad; Nadeem, Seema; Riyaz, Anila (Journal of Ayub Medical College Abbottabad, 2013)
Background: Smoking in orthotopic liver transplant (OLT) recipients has been associated with increased risk of vascular complications, cardiac events, graft failure and oesophegeal cancer. The aim of this study was to determine the effect of smoking on length of hospital stay post OLT and also to audit support provided to these patients. Methods: This was a retrospective study carried out in the Liver Transplant Unit, St James University Hospital, UK from 1979 to 2005. One hundred seventy-four 174 adult patients who had undergone OLT in this hospital during this time with a follow-up of at least 2 years after transplantation were included. Results: One hundred seventy-four 174 patients (mean age 52.2 years) responded by answering the questionnaire. Answers were analysed using relevant statistical methods. Eighty 80 patients had a smoking history (ever-smoked) while 94 were non-smokers (never-smoked). Out of 56 patients with a smoking history, 46% (n=26) were offered advice and only 18% (n=10) were offered any support. Of the 26 patients smoking at the time of OLT, 58% (n=15) were offered advice and only 19% (n=5) had been offered support. There was no significant difference in length of hospital stay post OLT between patients who had never-smoked and ever-smoked (p=0.780). In addition, smoking at the time of OLT had no significant impact on length of hospital stay (p=0.922). Conclusions: Smoking per se does not seem to increase hospital stay post OLT. Patients should be adequately counselled about smoking post OLT. Support mechanisms, including better awareness among doctors and allied healthcare workers should be made available to tackle this problem. Keywords: smoking, orthotopic liver transplant, OLT